2022
DOI: 10.3390/curroncol29110660
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Synchronous Brain Metastasis Incidence and Mortality in the United States: Ten-Year Multicenter Experience

Abstract: Background: Large epidemiological studies describing the trends in incidence rates and mortality of synchronous brain metastases (SBMs) are lacking. The study aimed to provide a comprehensive understanding of the changes in the incidence and mortality of SBMs over the previous ten years. Methods: Trends in the incidence of solid malignancies outside of the CNS in patients with SBMs and incidence-based mortality rates were assessed using data from the Surveillance, Epidemiology, and End Results database. Joinpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The natural history of progression from primary cancer to BM varies depending on the site of the primary tumor. According to a study analyzing the incidence and mortality of synchronous BM in the United States, the most common primary tumor site in patients with synchronous BM was the lung (80.3%) [ 21 ]. Likewise, in our study, lung cancer was the most frequently diagnosed at the same time as the primary tumor at 52.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of progression from primary cancer to BM varies depending on the site of the primary tumor. According to a study analyzing the incidence and mortality of synchronous BM in the United States, the most common primary tumor site in patients with synchronous BM was the lung (80.3%) [ 21 ]. Likewise, in our study, lung cancer was the most frequently diagnosed at the same time as the primary tumor at 52.8%.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the incidence of Helicobacter pylori -related cancers showed a significant downward trend from 2000 to 2019 and identified the racial/ethnic and geographic disparities in incidence rates. In addition, the demographic disparities in the incidence rates of SBMs [ 95 ], gliomas [ 74 ], and thyroid cancer [ 72 ] have been reported using this approach. The Rate Session in SEER*Sat software can be used to obtain the data when demographic covariables are considered in the exposure indicator and the outcome is a cancer diagnosis.…”
Section: Study Designsmentioning
confidence: 99%
“…Nonetheless, the opportunity to participate in prospective randomized clinical trials (RCTs) is typically only available to a limited number of patients with breast cancer brain metastasis (BCBM). Design challenges, including heterogeneity of patients, varying definitions of clinical end points, and different methods to assess these end points, have led to excluding most patients with BCBM from RCTs [ 5 , 6 ]. Consequently, while the incidence and survival duration have expanded, clinical research methods for BCBM remain limited [ 7 ].…”
Section: Introductionmentioning
confidence: 99%